Dye-sensitized solar cells - Dai, Songyuan (GREEN alternative energy resources ;, 2022)
"The operation of everything in the universe needs a special "material"-energy. The earth is no exception. There are many kinds of energy sources on earth. But where does the earth's energy come from? The answer is that everything grows under the sun. Developing renewable energy is of strategic importance to achieve sustainable energy supply. Simulating natural photosynthesis is the ultimate goal of effi cient solar energy conversion. Photovoltaic technology has been widely used in industry and will be one of the major energy sources in the future. Developing new materials and structures, the photoelectric conversion efficiency of solar cells will be improved day by day, and solar cells will attract more and more attention. This book presents principles of solar photovoltaic conversion, and introduces the physical and chemical processes involved. Mechanisms which affect solar cell performance are also discussed."--